2007
DOI: 10.1158/1078-0432.ccr-07-1398
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pathologic Staging: Defining Stage II Disease

Abstract: Tumor stage remains the most important determinant of prognosis in colorectal cancer and is the basis of all authoritative patient management guidelines. The pathologic assessment of stage II disease is especially critical because it may help to identify patients at additional risk for whom surgery alone may not be curative. Accurate analysis of regional lymph nodes, extent of tumor penetration, and circumferential resection margins constitute the most crucial issues. For assignment of pN0, adequacy of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 108 publications
4
89
0
6
Order By: Relevance
“…Although h-catenin expression was found to be related to local recurrence in univariate analysis, it was not selected as an independent predictor of this outcome. We have shown previously that h-catenin is associated with an infiltrating tumor margin, whereas this margin itself is significantly more common in budding versus nonbudding tumors (21,29). In addition, Brabletz et al found an increasing expression of this protein from the tumor center to the tumor margin (36).The lack of independence of h-catenin on recurrence is therefore likely due to its association with features that themselves are stronger predictors of recurrence.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although h-catenin expression was found to be related to local recurrence in univariate analysis, it was not selected as an independent predictor of this outcome. We have shown previously that h-catenin is associated with an infiltrating tumor margin, whereas this margin itself is significantly more common in budding versus nonbudding tumors (21,29). In addition, Brabletz et al found an increasing expression of this protein from the tumor center to the tumor margin (36).The lack of independence of h-catenin on recurrence is therefore likely due to its association with features that themselves are stronger predictors of recurrence.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, an infiltrative tumor margin diagnosed at low magnification is strongly associated with the presence of tumor budding defined as the transition from glandular structures to single cells or clusters of up to four cells at the invasive front and observed at high magnification (29,30). Tumor budding itself has been shown to have independent prognostic value in colorectal cancer and may be the most important prognostic indicator after lymph node spread (30).…”
Section: Discussionmentioning
confidence: 99%
“…3 Therefore, additional risk assessment is of utmost importance in these patients. 3 Different histopathological prognostic markers have been assigned to CRC patients, namely histomorphological variants of CRC, tumour differentiation, lymphatic and venous invasion, perineural invasion, tumour budding, tumour necrosis and inflammatory response. 4 Importantly, novel prognostic markers must not only be accurate, but also easily accessible on hematoxylin-eosin stained specimens and broadly applicable.…”
Section: Amp Studentmentioning
confidence: 99%
“…1 Stage according to the American Joint Committee on Cancer (AJCC)/Union Internationale Contre le Cancer (UICC) tumor node metastasis (TNM) system remains the most important prognostic parameter and guidance for therapeutic decision making. 2 However, patients with an identical stage may experience considerably different clinical courses of disease. Thus, additional stage-independent pathologic parameters are warranted to identify patients who may benefit from adjuvant treatment.…”
mentioning
confidence: 99%
“…Although adjuvant chemotherapy is the standard approach in AJCC/UICC stage III patients, it is considered for AJCC/UICC stage II patients only in high-risk constellations, such as pT4 disease. 1,2 Tumor-related local inflammation has been proposed as a hallmark of cancer and is emerging as a novel prognostic parameter. 3,4 It is evident that multiple different cell types of the adaptive and innate immune system interact with cancer cells and may also have a prognostic value in colorectal cancers.…”
mentioning
confidence: 99%